'Juggling the glass balls ...': Workplace spirituality in women leaders - Mayer, C-H; Viviers, R.; Oosthuizen, R.; Surtee, S. (South African Journal of Higher Education, 2017)
This qualitative study explored workplace spirituality in women leadership in higher education institutions (HEIs). Interviews were conducted with women leaders of the Higher Education Research Service network across eight institutions. Observations were made in one organisation. Findings show that women leaders are highly aware of their spirituality and religious affiliation which influence their work and work spirituality. Workplace spirituality includes how women leaders approach life and work, how spirituality expands their concept of religion and how the interwoven concepts of spirituality and religion help them to manage their work optimally. The study was limited to a relatively small sample size of 23 women leaders and was further bound to the qualitative research methodology. This study provides valuable insights into workplace spirituality regarding women leaders in South African HEIs. The findings provide a base for future research on women leaders in organisations and for leadership training of women within HEIs.